Checklist of echinoderms caught as by-catch along the Algerian coast, with newly recorded species - Benarous, Ahlam; Mezali, Karim (Zootaxa, 2026)
Echinoderms are found across a wide bathymetric range. Generally, the deep-sea environments remain inaccessible for sampling, however, by-catch serves as an opportunistic source for collecting and studying marine invertebrates from different depths. In this study, samples were collected from three sectors of the Algerian coast: East (Annaba), Central (Algiers, Tipasa) and West (Mostaganem) between November 2021 and May 2024, and identified based on morphological criteria. A total of 26 echinoderm species were recorded. Two asteroids belonging to the order Valvatida are reported for the first time on the Algerian coast: Anseropoda placenta (Pennant, 1777) found in the western sector and Peltaster placenta (Müller & Troschel, 1842) in the eastern sector. The echinoid of the order Camarodonta, Gracilechinus acutus (Lamarck, 1816) is also recorded for the first time in the eastern and western sectors. In parallel, a detailed literature review allowed the documentation of all echinoderm species previously reported along the Algerian coast, bringing the total number of known echinoderm species to 72 to date.